De la décentralisation de la gestion forestière à une gouvernance locale des forêts communautaires et des redevances forestières au Sud-est Cameroun - Jérémie Mbairamadji (VertigO, 2009)
Public participation has been found essential for sustainable forest management and the decentralization of forest management has been identified as a mean to enhance such participation. This paper analyzes the impacts of decentralization on public participation as well as its influence on local management of community forests and timber royalties in Southeast Cameroon. It also explores solutions for a sound local forest governance model. In Southeast Cameroon, decentralization has led to the monopolisation of local decision-making by two actors and the introduction of new committees in charge of forest management at the village scale, which challenges traditional forest management practices. As a result, local populations are marginalised and participate poorly in the management of community forests and forest royalties. The forest governance model proposed in this paper suggests ways of improving Cameroon’s current forest law to empower local populations and forest management committees. These improvements will help to create interdependent relationships with a diffuse distribution of power among actors involved in forest management. Such types of relationships are critical to promote participative and sustainable management of community forests and forest royalties, particularly in a tropical environment.